KINERJA PENGELOLAAN KEUANGAN DESA DI DESA SUKA RAYA, KECAMATAN PANCUR BATU, KABUPATEN DELI SERDANG - Damayanti, Safira; Rangkuti, Mohammad Ridwan (Universitas Nusa Cendana, 2024)
The purpose of this study is to identify and describe how the community views on Village Financial Management and how the Performance of Village financial management in Suka Raya Village, Pancur Batu District, Deli Serdang Regency. This study uses descriptive research methods with a qualitative approach. Data collection techniques were carried out by interview, observation, documentation, literature, and secondary data. Research informants came from the Village Government, the Village Consultative Body (BPD), and community leaders. The results of this study are as follows: First, the performance responsiveness of the Suka Raya Village Government is still lacking because the village government is less responsive in dealing with problems in the community. Second, the responsiveness of the village government has carried out activities in implementing the program in accordance with the principles of correct administration or in accordance with organizational policies. Third, the accountability of the village government is not fully responsible for what has been done because there are still complaints from the community. Keywords: Performance; Village Financial Management; Responsiveness; Responsiveness; Accountability